Fishery, population dynamics and stock structure of frigate tuna Auxis thazard (Lacepede, 1800) exploited from Indian waters - Ghosh, Shubha Deep (Indian Journal of Fisheries, 2012)
The fishery, population characteristics and stock estimates of frigate tuna Auxis thazard (Lacepede, 1800) from Indian waters was studied during 2006 – 2010. The average annual catch was 11,157 t, which contributed to 13.2% of the total tuna catches. The length–weight relationship showed that growth was allometric for the species. Length at first maturity estimated was 29.7 cm and fecundity 8,07,986. The von Bertalanffy growth equation derived was: Lt = 57.95 [1 - e - 1.2 (t + 0.0075)]. Growth performance index was 3.605 and the length at first capture 32.83 cm. The natural mortality, fishing mortality and total mortality were 1.65, 3.24 and 4.89 respectively and with an exploitation ratio 0.66. Emax estimated was 0.778, which is higher than the present exploitation, indicating scope for further exploitation. Maximum sustainable yield estimated was 13,100 t and the yield per recruit 332.3 g. Maximum yield and yield/recruit was obtained by doubling the present fishing effort, but at the increased fishing effort, the increase in yield is only 2.93%which indicates that the present level of fishing can be continued.